Postpartum Depression: Screening, Diagnosis, and Management Programs 2000 through 2010. (30th July 2012) - Yawn, Barbara P.; Olson, Ardis L.; Bertram, Susan; Pace, Wilson; Wollan, Peter; Dietrich, Allen J.
Abstract : The value and appropriateness of universal postpartum depression (PPD) screening remains controversial in the United States. To date, several PPD screening programs have been introduced and a few have been evaluated. Among those programs that have been evaluated, most report screening rates, diagnosis rates, or treatment initiation rates. Only four studies included patient outcomes such as the level of depressive symptoms at 6 to 12 months postpartum, and only two reported success in improving outcomes. Program characteristics that appear to result in low rates of diagnosis and followup after PPD screening include requirements for a formal psychiatric evaluation, the need to refer women to another site for therapy, and failure to integrate the PPD screening into the care provided at the woman's or her child's medical home. The two programs that reported improved outcomes were both self-contained within primary care and included specific followup, management, and therapy procedures. Both resulted in the need for outside referrals in less than 10% of women diagnosed with postpartum depression. Future studies should be based on the successful programs and their identified facilitators while avoiding identified barriers. To affect policies, the future program must report maternal outcomes going beyond the often reported process outcomes of screening, referral, and therapy initiation rates.